Imaging and pathological characteristics of hepatosplenic EBV-positive inflammatory follicular dendritic cell sarcoma - Chen, Yang-Yang; Wang, Peng-Ming; Deng, Li-Zhu; Li, Pei-Heng; Li, Chen-Guang; He, Yu-Hua; Chen, Feng; Yue, Jun-Yan (Frontiers in Oncology, 2025)
BackgroundThe aim of this study is to explore the CT and MRI characteristics of hepatosplenic Epstein-Barr virus (EBV)-positive inflammatory follicular dendritic cell sarcoma (IFDCS) and to correlate these findings with pathological characteristics to enhance diagnostic understanding.Case descriptionA retrospective analysis was conducted on 16 patients with surgically confirmed hepatosplenic EBV-positive IFDCS, who underwent CT and MRI between January 2015 and May 2024. Clinical, pathological, and imaging data were evaluated.ResultsHepatosplenic EBV-positive IFDCS primarily occurred in middle-aged adults, with a greater prevalence in females. All cases presented as solitary, well-defined masses, either round or oval in shape. Calcification was noted in one case, while necrosis and cystic degeneration were observed in nine cases. Contrast-enhanced CT and MRI showed that 15 cases exhibited heterogeneous, mild to moderate persistent uneven enhancement of the tumor parenchyma, with most lesions appearing hypodense or hypointense in the delayed phase. The majority of cases showed a hypodense or hypointense capsule with delayed enhancement. Solid tumor components appeared hyperintense on diffusion-weighted imaging (DWI), with apparent diffusion coefficient values similar to those of the spleen. One case of hepatic EBV-positive IFDCS exhibited an atypical enhancement pattern characterized by rapid wash-in and slow wash-out.ConclusionMRI proved superior in visualizing the tumor capsule and providing qualitative diagnostic information, yielding crucial information for clinical diagnosis and preoperative evaluation.